When chicken manure compost meets iron nanoparticles: an implication for the remediation of chlorophenothane-polluted riverine sediment. Issue 4 (11th March 2022) - Song, Biao; Yin, Zhuo; Almatrafi, Eydhah; Sang, Fan; Shen, Maocai; Xiong, Weiping; Zhou, Chengyun; Liu, Yang; Zeng, Guangming; Gong, Jilai
Abstract : The addition of nZVI could improve the degradation efficiency for chlorophenothane using chicken manure compost, while the compost mitigated the negative effect of nZVI on the bacterial community structure in sediment. Abstract : The remediation of contaminated sediment is an intractable problem as both the remediation efficiency and the ecological environmental impact should be carefully considered. In this study, nanoscale zero-valent iron (nZVI) was applied to assist the remediation of chlorophenothane (DDT)-polluted sediment by chicken manure compost. The response of sediment bacterial communities to the remediation treatments was evaluated a month later after two strategies of adding the remediation materials (simultaneous and phased) were implemented. Using nZVI could enhance the degradation efficiency for chlorophenothane with the compost. Compared with the simultaneous addition of chicken manure compost and nZVI at the beginning of remediation, using nZVI as a forerunner followed by adding the compost a week later further enhanced p, p ′-DDT degradation but increased the ∑DDT residual amount. The used chicken manure compost increased the richness, evenness, and diversity of sediment bacterial communities. According to β-diversity analysis, the compost made a greater difference in the bacterial communities than nZVI at 0.25 wt%, 0.5 wt%, and 1.0 wt%. Using 0.5 wt% nZVI could help to activate the bacterial metabolism in the compost-remediated sediment and increase functional abundance for DDT degradation. This study contributes to the improvement of sediment remediation technologies and the understanding of bacterial community variations in chlorophenothane-contaminated sediment remediated with chicken manure compost and nZVI.